Somatic piRNAs and Transposons are Differentially Expressed Coincident with Skeletal Muscle Atrophy and Programmed Cell Death - Tsuji, Junko; Thomson, Travis; Brown, Christine; Ghosh, Subhanita; Theurkauf, William E.; Weng, Zhiping; Schwartz, Lawrence M. (Frontiers in Genetics, 2021)
PIWI-interacting RNAs (piRNAs) are small single-stranded RNAs that can repress transposon expression via epigenetic silencing and transcript degradation. They have been identified predominantly in the ovary and testis, where they serve essential roles in transposon silencing in order to protect the integrity of the genome in the germline. The potential expression of piRNAs in somatic cells has been controversial. In the present study we demonstrate the expression of piRNAs derived from both genic and transposon RNAs in the intersegmental muscles (ISMs) from the tobacco hawkmoth Manduca sexta. These piRNAs are abundantly expressed, ~27 nt long, map antisense to transposons, are oxidation resistant, exhibit a 5’ uridine bias, and amplify via the canonical ping-pong pathway. An RNA-seq analysis demonstrated that 19 piRNA pathway genes are expressed in the ISMs and are developmentally regulated. The abundance of piRNAs does not change when the muscles initiate developmentally-regulated atrophy, but are repressed coincident with the commitment of the muscles undergo programmed cell death at the end of metamorphosis. This change in piRNA expression is correlated with the repression of several retrotransposons and the induction of specific DNA transposons. The developmentally-regulated changes in the expression of piRNAs, piRNA pathway genes, and transposons are all regulated by 20-hydroxyecdysone, the steroid hormone that controls the timing of ISM death. Taken together, these data provide compelling evidence for the existence of piRNA in somatic tissues and suggest that they may play roles in developmental processes such as programmed cell death.